Development of Conversational Text Teaching Materials for Indonesian Language Subjects Using Image Media for Class V Elementary UPT SPF Number 105272 Purwodadi Sunggal 2023-2024 - Beby Lidia Zuliani; Rahmat Kartolo; Sutikno Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
In the reality of education in the field, many educators still use conventional teaching materials, namely ready-to-use teaching materials, just buy, instant, without efforts to plan, prepare, and compile their own. Thus, the risk obtained is that the teaching materials they use are less attractive. An educator is required to be creative to be able to compile teaching materials that are innovative, varied, interesting, contextual, and in accordance with the level of student needs. Unfortunately, there are still many educators who still use conventional teaching materials, namely ready-to-use teaching materials, just buy, instant, without efforts to plan, prepare, and arrange their own and do not attract children's attention in learning. So image media is used as a development effort in Indonesian learning. This study aims to determine the quality of teaching materials based on the validation of material experts and media experts, determine the attractiveness of teaching materials based on student responses, and determine the average increase in student learning achievement based on pretest and postes scores. This research was carried out at UPT SPF State Elementary School Number 105272 Purwodadi Sunggal for the 2023-2024 Learning Year. This research is development research. The subjects of the study were 36 students of grade V of UPT SPF State Elementary School Number 105272 Purwodadi Sunggal for the 2023-2024 Learning Year. The data collection techniques used are tests, questionnaires, and documentation. The data analysis techniques used are percentages and averages. The overall quality of teaching materials is good with a percentage of 78%. The results of the attractiveness of teaching materials based on student responses in limited trials obtained a percentage of 87% with a very interesting category, while in large group trials a percentage of 85% was obtained with a very interesting category.